Analysis of the Desorption Capacity of Pb2+ and Cu2+ Metals on Silica and Silica-Chitosan Adsorbents - Faizul Puspitasari; La Harimu; Wa Ode Mulyana (Universitas Pendidikan Mandalika, 2025)
Studies have been conducted on the analysis of the desorption ability of Pb(II) and Cu(II) metals from silica and silica-chitosan adsorbents. This study aims to determine the desorption ability of Pb2+ and Cu2+ metals with variations in HCl concentrations using silica adsorbents and to determine the desorption ability of Pb2+ and Cu2+ metals with variations in HCl concentrations using silica-chitosan adsorbents. The parameters optimized in this study were concentration variations, namely 0.005 M, 0.01 M, and 0.02 M. The results of the study showed that silica adsorbents, Pb(II) metal desorption was best obtained at an HCl concentration of 0.02 M, which was 10.11%. Meanwhile, in silica adsorbents for Cu(II) metals, the best desorption was also obtained at an HCl concentration of 0.02 M, which is 0.0753%. In the silica-chitosan adsorbent, the best Pb(II) metal desorption was obtained at an HCl concentration of 0.01 M, which is 0.0298%, while the best desorption of Cu(II) metal was obtained at an HCl concentration of 0.01 M, which was 12.0684%